Write the expression as the logarithm of a single quantity
3[(ln x) -2ln(x^2+1)]+2 ln 5?
2 answers
ln{5^2 * [x / (x^2 + 1)^2]^3}
ln ( a ^ n ) = n * ln a
So:
2 ln 5 = ln ( 5 ^ 2 ) = ln 25
Now:
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + 2 ln 5 =
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + ln 25 =
3 * ( ln x ) - 3 * 2 ln ( x ^ 2 + 1 ) + ln 25 =
3 ( ln x ) - 6 ln ( x ^ 2 + 1 ) + ln 25
_________________________________
Remark:
ln ( a ^ n ) = n * ln a
3 ( ln x ) = ln ( x ^ 3 )
6 ln ( x ^ 2 + 1 ) = ln ( x ^ 2 + 1 ) ^ 6
ln ( a * b ) = ln a + ln b
ln ( x ^ 3 ) + ln 25 = ln ( 25 * x ^ 3 ) = ln ( 25 x ^ 3 )
ln ( a / b) = ln a - ln b
ln ( x ^ 3 ) + ln 25 - ln [ ( x ^ 2 + 1 ) ^ 6 ] = ln [ 25 x ^ 3 / ( x ^ 2 + 1 ) ^ 6 ]
_________________________________
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + 2 ln 5 = ln [ 25 x ^ 3 / ( x ^ 2 + 1 ) ^ 6 ]
So:
2 ln 5 = ln ( 5 ^ 2 ) = ln 25
Now:
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + 2 ln 5 =
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + ln 25 =
3 * ( ln x ) - 3 * 2 ln ( x ^ 2 + 1 ) + ln 25 =
3 ( ln x ) - 6 ln ( x ^ 2 + 1 ) + ln 25
_________________________________
Remark:
ln ( a ^ n ) = n * ln a
3 ( ln x ) = ln ( x ^ 3 )
6 ln ( x ^ 2 + 1 ) = ln ( x ^ 2 + 1 ) ^ 6
ln ( a * b ) = ln a + ln b
ln ( x ^ 3 ) + ln 25 = ln ( 25 * x ^ 3 ) = ln ( 25 x ^ 3 )
ln ( a / b) = ln a - ln b
ln ( x ^ 3 ) + ln 25 - ln [ ( x ^ 2 + 1 ) ^ 6 ] = ln [ 25 x ^ 3 / ( x ^ 2 + 1 ) ^ 6 ]
_________________________________
3 [ ( ln x ) - 2 ln ( x ^ 2 + 1 ) ] + 2 ln 5 = ln [ 25 x ^ 3 / ( x ^ 2 + 1 ) ^ 6 ]